Analysis of fuel performance under normal operation conditions of MicroURANUS: Micro long-life lead-bismuth-cooled fast reactor - Mun, Jiwon; Kim, Hyeong-Jin; Ryu, Ho Jin (Frontiers in Energy Research, 2022)
An innovative ultra-long-life lead-bismuth eutectic (LBE)-cooled fast reactor called MicroURANUS has been designed to prevent severe accidents. It utilizes the remarkable natural circulation capability of the LBE coolant. Furthermore, it can be operated at 60 MWth without refueling for 30 effective full-power years (EFPY). In this study, the thermal and mechanical performance of the hottest fuel rod of MicroURANUS was evaluated by modifying the fuel performance code FRAPCON-4.0, which is the normal operation fuel performance code for light water reactors (LWRs). A plutonium generation model was added to consider changes in the physical properties of the UO2 fuel. Furthermore, mechanical and oxidation models of 15-15 Ti were added, and the coolant models were modified for liquid metal. According to the unique design of MicroURANUS, a maximum low linear power density of 12.5 kW/m ensures that the hottest fuel rod can operate below the safety limit. A low fuel temperature provides a large safety margin for fuel melting, as well as low-pressure build-up fission gas release. In addition, low inlet and outlet coolant temperatures of 250 ℃ and 350 ℃ cause the cladding to display a low degree of swelling (a maximum diametral strain of 1.5%) while maintaining high mechanical integrity with negligible cumulative damage fraction (CDF). The modified fuel performance code for lead-cooled fast reactors exhibited the capability to be utilized for fuel performance evaluation and design feedback of MicroURANUS.